Exploring coumarin potentialities: development of new enzymatic inhibitors based on the 6-methyl-3-carboxamidocoumarin scaffold. Issue 55 (20th May 2016) - Fonseca, A.; Matos, M. J.; Reis, J.; Duarte, Y.; Gutiérrez, M.; Santana, L.; Uriarte, E.; Borges, F.
Abstract : Novel 6-methyl-3-carboxamidocoumarins were synthesized by an effective three step synthetic strategy and screened towards MAO, AChE and BuChE enzymes. Abstract : Novel 6-methyl-3-carboxamidocoumarins (compounds4–15 ) were synthesized by an effective three step synthetic strategy and screened towards MAO, AChE and BuChE enzymes. In general, the compounds act as selective MAO-B inhibitors. Compound11 is highlighted as a potent (IC50 h MAO-B = 4.66 nM), reversible and non-competitive MAO-B inhibitor.